2008
DOI: 10.1097/brs.0b013e31816b46a5
|View full text |Cite
|
Sign up to set email alerts
|

Early Histologic Changes Following Polymethylmethacrylate Injection (Vertebroplasty) in Rabbit Lumbar Vertebrae

Abstract: Injection of PMMA in rabbit lumbar vertebral bodies produces early, focal bone necrosis in only half of cases, suggesting that competency of the cement-bone interface is reasonable in most cases. No evidence of intraosseous neural tissue damage was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 41 publications
5
35
1
3
Order By: Relevance
“…There are several proposed analgesic mechanisms involved in the treatment. Firstly, PMMA monomer is cytotoxic, resulting in tumor cell dehydration, solidify and finally apoptosis [10][11][12]. Secondly, stabilization of the small fractures prevents stimulation of the pain nerve endings caused by squeezing up and down and left-right frictions.…”
Section: Discussionmentioning
confidence: 99%
“…There are several proposed analgesic mechanisms involved in the treatment. Firstly, PMMA monomer is cytotoxic, resulting in tumor cell dehydration, solidify and finally apoptosis [10][11][12]. Secondly, stabilization of the small fractures prevents stimulation of the pain nerve endings caused by squeezing up and down and left-right frictions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent study, the temperature required to ablate nociceptive nerve endings was found to be 42°C to 45°C. 32 In our cadaver cranioplasty model (experiment 2), the PMMA was approximately 12 mm thick at its thickest point, which explains the much higher temperatures relative to those obtained in experiment 1. The 5°C difference in maximum temperature reached at locations A (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…A bone temperature of 47°C for 1 minute has been shown to cause osteonecrosis [4]. Bone temperatures exceeding 88.8°C have been recorded when cementing hip resurfacing components in an experimental model [5], and injection of PMMA cement in to rabbit lumbar vertebrae has been shown to produce focal bone necrosis [6]. It has also been found that cooling the femoral canal in a model before cementing a femoral stem led to lower bone-cement interface temperatures and higher shear strength of the stem:cement interface [7].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly one study using ovine models found that thermonecrosis did not occur despite temperatures exceeding 49.3° [11] although this contradicts several other papers which suggest that thermally induced bone injury may be significant [5,6,12]. …”
Section: Discussionmentioning
confidence: 97%